Religious Symbols in Public Schools: Key Issues and Debates - Aleš Črnič; Anja Pogačnik (Center for Educational Policy Studies Journal)
When discussing Religious Education, the topic of religious symbols in educational spaces is largely overlooked in academic literature and often side-lined in political considerations as well. This paper examines the issue of religious symbols in public schools by highlighting two foci: how the Muslim veil is managed in public schools in select European countries and zooming in on specific suggestions for managing religious symbols in public schools in Slovenia. By combining a broader, comparative perspective with practical, small-scale policy suggestions, the paper highlights the need to include a discussion of religious symbols in public schools in our academic and political considerations of religion and education.